OVERALL INDEX OF POLLUTION (OIP) FOR TIGRIS RIVER, BAGHDAD CITY, IRAQ - Z. Z. Al-Janabi,; F.M. Hassan,; A. H. M. J. Al-Obaidy, (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2024)
This study aimed to identify the pollution extent in the Tigris River within Baghdad city by applying the Overall index of Pollution (OIP). Monthly water samples were collected from five sites along the Tigris River during the wet and dry seasons of 2020-2021. Eleven parameters were selected to conduct the study; Total Dissolved Solids, Turbidity, Chloride, Dissolved Oxygen, pH, Total Hardness, Fluoride, Nitrate, Sulfate, Biochemical oxygen demand, and Total Coliform. The OIP ranges from 2.46 to 1.96 in the dry season and 2.02 to 1.91 in the wet season. Results revealed that Tigris River water is categorized from slightly polluted to acceptable according to OIP classification. The current study's finding lies in a wet season where the values of OIP are less in most of the sites, which may be related to the increased precipitation in the winter months.